Oceanographic time series at South Cape from April 2022 to April 2023 ... - Ferré, Benedicte (DataverseNO, 2024)
Time series of temperature, salinity, pressure, pH and Oxygen obtained from a Seabird SeapHOx sensor deployed south of Svalbard to monitor an intense seepage. Conservative temperature, potential temperature and absolute salinity were calculated and added to the dataset. ...